Pandemia da Covid-19: o governo de Jair Bolsonaro perante o direito à vida e à saúde - Lopes, Liriane Wanderley de Sousa Leite (2023)
The Covid-19 pandemic was a critical moment that humanity went through, however, along with it, the scientific community was hand in hand to minimize the crisis and the discovery of a targeted vaccine for a disease that until then had not been known. Adequate treatments, on the other hand, it was only known that the closing of borders, social distance and the use of a mask were the only allies to fight this incipient battle. Alongside the related events, the present study intends to analyze the Covid-19 pandemic in the world and in Brazil and, if the actions of the federal government were in accordance with the measures adopted with the necessary scientific technicality, as well as in accordance with international legislation of Human Rights to life and health, precepts these signatories for Brazil. The digression carried out throughout the research can be seen that the federal government, in the figure of the then president Bolsonaro, exceeded several limits, whose denialist behaviors adopted led to the excess loss of almost 120 thousand lives, according to the study of Jurema Werneck and, according to the study by Pedro Hallal, there were approximately 450,000 lives lost, since the president assumed an anti-politics when he denied the decimating potential of the pandemic crisis, as head of state, he gave several negative examples, namely: he was against the use of a mask, against social isolation, disdained the use of the vaccine and encouraged the use of medication that was declared to be ineffective for the treatment of the disease, which even caused serious side effects. Furthermore, from a lexicographic perspective, the statements made by the then president about Covid-19 had a dramatic impact on combating the biggest health crisis that Brazil and the world have faced.